Physiologically-based pharmacokinetic predictions of intestinal BCRP-mediated drug interactions of rosuvastatin in Koreans - Bae, Soo Hyeon (Korean J Physiol Pharmacol, 2018)
It was recently reported that the C(max) and AUC of rosuvastatin increases when it is coadministered with telmisartan and cyclosporine. Rosuvastatin is known to be a substrate of OATP1B1, OATP1B3, NTCP, and BCRP transporters. The aim of this study was to explore the mechanism of the interactions between rosuvastatin and two perpetrators, telmisartan and cyclosporine. Published (cyclosporine) or newly developed (telmisartan) PBPK models were used to this end. The rosuvastatin model in Simcyp (version 15)'s drug library was modified to reflect racial differences in rosuvastatin exposure. In the telmisartan–rosuvastatin case, simulated rosuvastatin C(maxI)/C(max) and AUC(I)/AUC (with/without telmisartan) ratios were 1.92 and 1.14, respectively, and the T(max) changed from 3.35 h to 1.40 h with coadministration of telmisartan, which were consistent with the aforementioned report (C(maxI)/C(max): 2.01, AUC(I)/AUC:1.18, T(max): 5 h → 0.75 h). In the next case of cyclosporine–rosuvastatin, the simulated rosuvastatin C(maxI)/C(max) and AUC(I)/AUC (with/without cyclosporine) ratios were 3.29 and 1.30, respectively. The decrease in the CL(int,BCRP,intestine) of rosuvastatin by telmisartan and cyclosporine in the PBPK model was pivotal to reproducing this finding in Simcyp. Our PBPK model demonstrated that the major causes of increase in rosuvastatin exposure are mediated by intestinal BCRP (rosuvastatin–telmisartan interaction) or by both of BCRP and OATP1B1/3 (rosuvastatin–cyclosporine interaction).